Analysis of mathematical problem solving ability mathematical problem solving ability in terms of adversity quotient in problem based learning model class VIII Junior High School 2 Delitua - Pulungan, Khairunnisyah; Destini, Rita; Zahari, Cut Latifah (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study aims to determine the mathematical problem solving ability of students in terms of Adversity Quotient through the application of Problem Based Learning model in class VIII SMP Negeri 2 Delitua. This type of research uses qualitative research with descriptive type. The subjects used in this study amounted to 6 students, namely 2 subjects with high ability, 2 subjects with medium ability, and 2 subjects with low ability. The data collection techniques used were observation sheets, Adversity Quotient questionnaires, problem solving ability tests, interviews and documentation. Data processing and analysis using the Miles and Huberman technique which consists of 3 stages, namely data reduction, data presentation, and conclusion drawing or verification. The results showed that the Problem Based Learning (PBL) learning model was effectively applied to the mathematical problem solving ability of class VIII students of SMP Negeri 2 Delitua marked by the fulfillment of all indicators of students' mathematical problem solving ability. The mathematical problem solving ability of students with the climber type in the very good category, the camper type in the good category and the quitters type in the less category.